ICAN Practice & Revision Kit; Financial Accounting - Mayo-BPP (Yaba, Lagos BPP Publishers, 1989)
This publication specifically addressed all topics in the ICAN syllabus for Accounting.
includes index and illustrations
jbi, 20/03/2018
loans
Keywords: Accounting